?LOCAL DEVELOPMENT OF TSH RADIO IMMUNOASSAY AND IT'S EVALUATION (Biological Sciences - PJSIR, 1995)
Pakistan isan iodine deficientcountry,Thyroiddiseasesare verycommon andtheir investigation requires heavy foreign exchange to import relevant commercial kits. AEMC, Multan therefore tried to develop adequate and eco- nomical protocol for TSH radioimmunoassay.TSH-RIAprotocol supplied by the commercial source did not provide the desired quality and evaluation of thyroid diseases.Our method was therefore optimized using precision profile as the criteria of performance.Atotal of sixassay systemswerestudied,out of which the most precise one was selected. The new systemgives resultswithinexpectedlimits.The sensitivityof thesystem,0.3~lU/ml is suitable for low dose measurements. The working range, 0.6-25.1 ~lU/ml covers hypo, hyper and euthyroid levels of the hormone. Com- parison with other laboratoriesshows an agreementof values.Alowcost, locallydeveloped good qualityTSH RIAis therefore in our hand.